2021
DOI: 10.3390/vaccines9080912
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Protective Immunity in Sheep Vaccinated with a Combined Vaccine against Peste des Petits Ruminants and Sheep Pox

Abstract: In this study, the ability of the combined vaccine against peste des petits ruminants (PPR) (Nigeria strain 75/1) and sheep pox (SPP) (NISKhI strain) to form a protective immune response for 12 months in Kazakh breed fine-fleeced sheep aged 6–12 months was demonstrated. The duration of the protective immunity of immunized sheep from PPR and from SPP was evaluated using a serum neutralization test (SNT), followed by testing of the resistance of vaccinated sheep to infection with the field strain Kentau-7 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This makes it difficult to determine the true duration of immunity under field conditions, especially in endemic regions, since reinfections of vaccinated animals could boost the immune response without inducing clinical symptoms. A single vaccination with a live attenuated sheeppox vaccine has been shown to protect vaccinated sheep against sheeppox for at least 1 [ 29 ], 2 [ 30 , 31 ] or even 4 years [ 32 ]. Data in relation to the protection against LSDV is scarce, however.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it difficult to determine the true duration of immunity under field conditions, especially in endemic regions, since reinfections of vaccinated animals could boost the immune response without inducing clinical symptoms. A single vaccination with a live attenuated sheeppox vaccine has been shown to protect vaccinated sheep against sheeppox for at least 1 [ 29 ], 2 [ 30 , 31 ] or even 4 years [ 32 ]. Data in relation to the protection against LSDV is scarce, however.…”
Section: Introductionmentioning
confidence: 99%
“…while also thinking about other problems, such as hypocalcaemia, pregnancy toxaemia etc. Other studies on sheep and goat have also shown that antibody titres resulting from the administration of live attenuated PPR vaccines do not decrease significantly within 6 months after administration (Amanova et al., 2021 ; Kumar et al., 2014 ).…”
Section: Discussionmentioning
confidence: 95%
“…The antibodies developed were maintained for up to 6 months pv with insignificant fluctuations. Furthermore, a steady decrease in titer was observed, reaching only 1.9 log2 at the end of the experiment [87].…”
Section: Spp Vaccinesmentioning
confidence: 90%